[tex]a)\\\\ \frac{ 12-x }{4}= \frac{x+4 }{12}\ \ |*12\\\\4(x+4)=12(12-x)\\\\4 x+16=144-12x\\\\4x+12x=144-16\\\\16x=128\ \ |:16\\\\x=8[/tex]
[tex]b)\\\\\frac{ 3x-2}{4} =\frac{ 4x-5 }{3}\ \ |*12\\\\3(3x-2)=4(4x-5)\\\\9x-6=16x-20\\\\9x-16x=-20+6\\\\-7x=-14\ \ |:(-7)\\\\x=2[/tex]
[tex]c)\\\\ \frac{ x-3 }{6}=2(3x+1)\ \ |*6 \\\\x-3=12(3x+1)\\\\x-3=36x+12\\\\x-36x=12+3\\\\-35x=15\ \ |:(-35)\\\\x=-\frac{15}{35}=-\frac{3}{7}[/tex]
[tex]d)\\\\ 3(1-\frac{x}{3})= \frac{5x-1}{9}\\\\3-x= \frac{5x-1}{9}\ \ |*9\\\\27-9x=5x-1\\\\-9x-5x=-1-27\\\\-14x=-28\ \ |:(-14)\\\\x=2[/tex]